Techniques for remediation of pharmaceutical pollutants using metal organic framework - Review on toxicology, applications, and mechanism. (December 2022) - Sivaprakash, Baskaran; Rajamohan, Natarajan; Singaramohan, Dhanapriya; Ramkumar, Vanaraj; Elakiya, B. Tamil
Abstract: Treatment of recalcitrant and xenobiotic pharmaceutical compounds in polluted waters have gained significant attention of the environmental scientists. Antibiotics are diffused into the environment widely owing to their high usages, very particularly in the last two years due to over consumption during covid 19 pandemic worldwide. Quinolones are very effective antibiotics, but do not get completely metabolized due to which they pose severe health hazards if discharged without proper treatment. The commonly reported treatment methods for quinolones are adsorption and advanced oxidation methods. In both the treatment methods, metal organic frameworks (MOF) have been proved to be promising materials used as stand-alone or combined technique. Many composite MOF materials synthesized from renewable, natural, and harmless materials by eco-friendly techniques have been reported to be effective in the treatment of quinolones. In the present article, special focus is given on the abatement of norfloxacin and ofloxacin contaminated wastewater using MOFs by adsorption, oxidation/ozonation, photocatalytic degradation, electro-fenton methods, etc. However, integration of adsorption with any advanced oxidation methods was found to be best remediation technique. Of various MOFs reported by several researchers, the MIL-101(Cr)–SO3 H composite was able to give 99% removal of norfloxacin by adsorption. The MIL – 88A(Fe) composite and Fe LDH carbon felt cathode were reported to yield 100% degradation of ofloxacin by photo-Fenton and electro-fenton methods respectively. The synthesis methods and mechanism of action of MOFs towards the treatment of norfloxacin and ofloxacin as reported by several investigation reports are also presented. Graphical abstract: Image 1 Highlights: Applications of metal organic framework for removal of pharmaceutical components are discussed. Toxicological properties of norfloxacin and ofloxacin are presented. Action mechanisms of MOFs in treatment of quinolones are explained. Future scope and existing research gaps are identified.